The transport mechanism of bacterial Cu(+)-ATPases: distinct efflux rates adapted to different function - Raimunda, Daniel (2011)
Cu(+)-ATPases play a key role in bacterial Cu(+) homeostasis by participating in Cu(+) detoxification and cuproprotein assembly. Characterization of Archaeoglobus fulgidus CopA, a model protein within the subfamily of P(1B-1) type ATPases, has provided structural and mechanistic details on this group of transporters. Atomic resolution structures of cytoplasmic regulatory metal binding domains (MBDs) and catalytic actuator, phosphorylation, and nucleotide binding domains are available. These, in combination with whole protein structures resulting from cryo-electron microscopy analyses, have enabled the initial modeling of these transporters. Invariant residues in helixes 6, 7 and 8 form two transmembrane metal binding sites (TM-MBSs). These bind Cu(+) with high affinity in a trigonal planar geometry. The cytoplasmic Cu(+) chaperone CopZ transfers the metal directly to the TM-MBSs; however, loading both of the TM-MBSs requires binding of nucleotides to the enzyme. In agreement with the classical transport mechanism of P-type ATPases, occupancy of both transmembrane sites by cytoplasmic Cu(+) is a requirement for enzyme phosphorylation and subsequent transport into the periplasmic or extracellular milieus. Recent transport studies have shown that all Cu(+)-ATPases drive cytoplasmic Cu(+) efflux, albeit with quite different transport rates in tune with their various physiological roles. Archetypical Cu(+)-efflux pumps responsible for Cu(+) tolerance, like the Escherichia coli CopA, have turnover rates ten times higher than those involved in cuproprotein assembly (or alternative functions). This explains the incapability of the latter group to significantly contribute to the metal efflux required for survival in high copper environments.